2020
DOI: 10.1186/s12915-019-0732-7
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic activation of parvalbumin and somatostatin interneurons selectively restores theta-nested gamma oscillations and oscillation-induced spike timing-dependent long-term potentiation impaired by amyloid β oligomers

Abstract: Background: Abnormal accumulation of amyloid β 1-42 oligomers (AβO 1-42), a hallmark of Alzheimer's disease, impairs hippocampal theta-nested gamma oscillations and long-term potentiation (LTP) that are believed to underlie learning and memory. Parvalbumin-positive (PV) and somatostatin-positive (SST) interneurons are critically involved in theta-nested gamma oscillogenesis and LTP induction. However, how AβO 1-42 affects PV and SST interneuron circuits is unclear. Through optogenetic manipulation of PV and SS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 85 publications
2
68
0
Order By: Relevance
“…p > 0.05), and one-way ANOVA followed by Tukey's post hoc test (p, ***p < 0.001, **p < 0.01). Data are mean ± SEM with individual data values (dots) ◂ oscillations could be in part explained by additional excitation provided by optogenetic activation of SST/PV interneurons allowing for the activation of SST/PV interneuronal networks to a critical level for oscillations, which would otherwise show reduced activation due to the AβO-induced decrease in the excitation level in SST and PV interneurons (Hanson 2017;Schmid et al 2016;Park et al 2020). Indeed, optogenetic activation of SST and PV interneurons restored the sIPSC amplitudes to the level observed in DMSOinjected mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…p > 0.05), and one-way ANOVA followed by Tukey's post hoc test (p, ***p < 0.001, **p < 0.01). Data are mean ± SEM with individual data values (dots) ◂ oscillations could be in part explained by additional excitation provided by optogenetic activation of SST/PV interneurons allowing for the activation of SST/PV interneuronal networks to a critical level for oscillations, which would otherwise show reduced activation due to the AβO-induced decrease in the excitation level in SST and PV interneurons (Hanson 2017;Schmid et al 2016;Park et al 2020). Indeed, optogenetic activation of SST and PV interneurons restored the sIPSC amplitudes to the level observed in DMSOinjected mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Soluble AβO was prepared following the methods described in (Lambert et al 1998) with slight modification in Aβ oligomerization (Park et al 2020). Soluble Aβ 1-42 (Bechem) monomerization was achieved by dissolving it in 1,1,1,3,3,3-hexafluoro-2-propanol (HFIP, Sigma Aldrich) at a final concentration of 1 mM.…”
Section: Soluble Aβo Preparationmentioning
confidence: 99%
“…Improving Nav1.1 expression (Verret et al, 2012), enhancing γ-oscillatory activity in PV inhibitory interneurons by 40 Hz light flickering with/without 40 Hz auditory stimulation (Iaccarino et al, 2016;Adaikkan et al, 2019;Martorell et al, 2019), or transplanting Nav1.1-overexpressing interneurons (Verret et al, 2012;Martinez-Losa et al, 2018) could inhibit epileptiform phenomena and rescue cognitive deficits. Optogentic activation of PV and SST neurons rescued network oscillations (Chung et al, 2020;Park et al, 2020).…”
Section: Targeting Increased Numbers Of Gaba Inhibitory Interneuronsmentioning
confidence: 94%
“…In further support of a link between PV interneurons and symptoms of PICS, we found that theta or gamma oscillation, a neurophysiological phenomenon that is supported by PV interneuron function, correlates positively with time with novel object. In one recent study, it is reported that PV and SST interneurons play a key role in hippocampal theta-nested gamma oscillations and long-term potentiation [41]. This is further supported by findings that changes in cortical gamma oscillation power and/or frequency can lead to various behavioral and cognitive effects [26,39].…”
Section: Discussionmentioning
confidence: 78%